ADSORPTION CHARACTERISTICS, ISOTHERM AND KINETICS OF A NOVEL POLYHIPE/PULLULAN COMPOSITE FOR REMOVING CONGO RED DYE - San, Nevim; Mert, Emine Hilal; Kaya, Dila; Cira, Funda (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2016)
In this study the aim was to adsorb the organic, water soluble diazo dye Congo Red (CR) from water by using newly synthesized amine functional poly(high internal phase emulsion)/pullulan (polyHIPE/pullulan) composite. This novel semi-interpenetrating (semi-IPN) and amine functional macroporous polymer composite was prepared by the cross-linking of a glycidyl methacrylate (GMA) based high internal phase emulsion (HIPE) obtained by dispersing the aqueous phase (pullulan is dissolved in deionised water) in the continuous phase. Afterwards, modification of the resulting materials was carried out with 1,4-ethylene diamine (EDA). Using the data obtained from the conducted adsorption experiments, the adsorption isotherms were plotted and thermodynamical parameters for the adsorption process as well as the kinetic model were determined. It was shown that the adsorption of Congo Red onto polyHIPE/pullulan composite fitted Langmuir isotherm and followed pseudo second order kinetic model. The calculated Delta G degrees values lied between -58.2 kJ.mol(-1) and -61.2 kJ.mol(-1) which revealed that the Congo Red adsorption on polyHIPE/pullulan composite is spontaneous and exothermic. Calculated maximum q(m) value was 75.96 mg.g(-1) for 80 mg.L-1 CR at 323 K., and this 98.1 % decrease in batch dye concentration was obtained within the first 20 minutes of the adsorption reaction.
Keywords: Adsorption; polyHIPE composite; novel adsorbent; water treatment; congo red; WATER-TREATMENT PROCESSES; DISSOLVED AIR FLOTATION; AQUEOUS-SOLUTION; GLYCIDYL METHACRYLATE; POLYHIPE MONOLITHS; WASTE-WATER; AMINE FUNCTIONALIZATIONS; ACTIVATED CARBON; DIAZO DYE; EQUILIBRIUM; Environmental Sciences & Ecology